Pelatihan Pembuatan Nano Liquid Aromaterapi bagi Kader PKK Desa Wajok Hilir di Kabupaten Mempawah: Training on Manufacturing Aromatherapy Nano liquid for PKK Cadres in Wajok Hilir Village in Mempawah District - Pratiwi, Liza; Wijianto, Bambang; Fahrurroji, Andhi; Yuswar, Muhammad Akib (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
So far, essential oils have only been used as perfume and sold as raw material. On average, residents of Wajok Hilir village have yards covered with essential oil-producing plants such as lavender, lemongrass, and coconut. The aim of the PKM Program is training in utilizing community resources to make essential oils for aromatherapy in nano-liquid preparations. The development of this product must be oriented towards developing a practice that is easy to apply and environmentally friendly without ignoring environmental health. The solution to overcome existing problems is to provide knowledge to partners about the benefits of nano liquid preparations as aromatherapy and mosquito repellent and training on using essential oils as aromatherapy. Pharmacists provided training on making "nano liquid" products. This training activity will involve PKK cadres from Wajok Hilir village. The output target of this activity is to increase the level of quality empowerment of partners by driving sustainable activity programs from product results. This service activity showed that the 31 participants comprised the majority of women and homemakers, 77.4% with a high school education level. The results of measuring participants' knowledge and skills showed an increase in the pre-test and post-test scores, which were 55.5 and 78.33, respectively. In conclusion, the service activities that have been carried out have increased the knowledge and abilities of participants regarding the use of essential oils as aromatherapy in the form of nano-liquid preparations.